2022
DOI: 10.1097/sla.0000000000005561
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Safety of Ambulatory Surgery as the Next Management Paradigm in Colorectal Resection Surgery

Abstract: Background: Current clinical dogma favors universal inpatient admission after colorectal resection particularly in the presence of an anastomosis. Objective: We evaluate the feasibility and safety of ambulatory surgery in carefully selected patients undergoing colorectal resection/anastomosis. Methods: Between October 2020 and October 2021, all patients undergoing colorectal resection/anastomosis meeting specific criteria {no major comorbidity [American Society of Anesthesiologist (ASA) <4], not on therape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…All studies reported on readmission rates, but only six compared their outcomes to conventional ERAS management. 22 28 29 32 33 35 Saadat, found a significant decrease in readmission rate in the 24 hours discharge group (24 hours discharge group 6.3% versus conventional ERAS 9.3%, p < 0.001). 29 The other five studies showed comparable readmission rates between groups.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…All studies reported on readmission rates, but only six compared their outcomes to conventional ERAS management. 22 28 29 32 33 35 Saadat, found a significant decrease in readmission rate in the 24 hours discharge group (24 hours discharge group 6.3% versus conventional ERAS 9.3%, p < 0.001). 29 The other five studies showed comparable readmission rates between groups.…”
Section: Resultsmentioning
confidence: 93%
“…However, only five studies compared outcomes to conventional ERAS management. 24,28,32,33 None of the comparing studies showed a significant difference in complications rates. A few smaller sized studies observed no complications in their 24 hours discharge study participants.…”
Section: Complicationsmentioning
confidence: 97%
See 3 more Smart Citations